2016
DOI: 10.1182/blood-2015-11-636464
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for hemostatic dysfunction in malaria pathogenesis

Abstract: Severe Plasmodium falciparum malaria remains a leading cause of mortality, particularly in sub-Saharan Africa where it accounts for up to 1 million deaths per annum. In spite of the significant mortality and morbidity associated with cerebral malaria (CM), the molecular mechanisms involved in the pathophysiology of severe malaria remain surprisingly poorly understood. Previous studies have demonstrated that sequestration of P falciparum–infected erythrocytes within the microvasculature of the brain plays a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 99 publications
1
69
0
3
Order By: Relevance
“…However, other tissues likely contribute to circulating syndecans and glycosaminoglycans. We are aware that CM has a complex pathogenesis that includes dysregulated inflammatory pathways and a poorly regulated coagulation system (63)(64)(65). Thus, even though several inhibitors for various pathways potentially affecting glycocalyx shedding have been explored in this paper, we may have missed important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, other tissues likely contribute to circulating syndecans and glycosaminoglycans. We are aware that CM has a complex pathogenesis that includes dysregulated inflammatory pathways and a poorly regulated coagulation system (63)(64)(65). Thus, even though several inhibitors for various pathways potentially affecting glycocalyx shedding have been explored in this paper, we may have missed important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The increased binding (at standardised assay conditions of 2% parasitaemia and 5% haematocrit) to EC correlated with increased parasitaemia, but with decreased platelet numbers. Activation of platelets and platelet consumption leads to a pro-coagulant state characterised by an increase in thrombin and von Willebrand factor, which are demonstrated in SM (Dorovini-Zis et al, 2011;O'Sullivan et al, 2016;Thachil, 2017). A recent study in children recruited from the same hospital in 2015-2016 showed that low platelet levels were also associated with retinopathy-positive CM cases and brain swelling (Kessler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation between peripheral platelets and binding intensity is interesting as thrombocytopenia has been used as a predictor for malaria (Lampah et al, 2015;Thachil, 2017) and specifically for P. falciparum SM (Gerardin et al, 2002;Cserti-Gazdewich et al, 2012). In addition, anti-coagulation and endothelial protective pathways are affected in CM through a decrease in EPCR and thrombomodulin and thus dysfunction of the activated protein C pathway (Moxon et al, 2013(Moxon et al, , 2015O'Sullivan et al, 2016). Some studies have shown that CM cases have more platelets localised in the brain microvasculature Dorovini-Zis et al, 2011) and show increased platelet-mediated clumping of IE (Pain et al, 2001;Wassmer et al, 2008) and platelet involvement in the adhesion of IE to human microvascular EC lacking CD36 (Wassmer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…19 For example, high parasitemia primarily of Falciparum malaria, may be associated with DIC, and high mortality. 20 Factors involved in the development of DIC complicating infections are microbial membrane constituents, such as lipopolysaccharide or lipoteichoic acid, or exotoxins (e.g. Staphylococcaltoxin), evoking a strong immune response and release of cytokines.…”
Section: Clinical Settingsmentioning
confidence: 99%